Bi-level strategic bidding model for P2G facilities considering a carbon emission trading scheme-embedded LMP and wind power uncertainty - Zhang, Rufeng; Jiang, Tao; Li, Fangxing; Li, Guoqing; Chen, Houhe; Li, Xue (International journal of electrical power & energy systems, 2021)
•A novel stochastic bi-level strategic bidding model for P2G facility is proposed.•Carbon emission trading scheme (CETS) and its impact on LMP are considered.•The bi-level model is converted into mixed-integer linear programming (MILP).•The proposed bidding model can increase the profit of P2G facility.•CETS can increase the profit of P2G facilities and reduce carbon emission. As an emerging energy storage technology for renewable power utilization, power-to-gas (P2G) requires efficient bidding strategies to increase profit. This paper proposes a bi-level strategic bidding model for P2G with the consideration of a carbon emission trading scheme (CETS), an embedded locational marginal price (LMP) and wind power uncertainty, where the upper level model aims to maximize the profit of P2G facilities and the lower level model carries out the market clearing process. Under a CETS, a P2G facility purchases electricity power according to the LMP and is assumed to sell synthetic natural gas (SNG) and carbon emission permits for revenue. The electricity market clearing process is represented by a stochastic low carbon economic dispatch (ED) model considering the CETS, P2G and wind power uncertainty. On this basis, the formulation of a CETS embedded LMP (CETS-LMP) is presented and analyzed here. The bi-level model is reformulated and converted into mixed-integer linear programming (MILP) using strong duality theory. Case studies performed on a modified PJM 5-bus system and an IEEE 118-bus system verify the effectiveness of the proposed model and demonstrate that considering the CETS can increase the profit of P2G facilities and reduce carbon emission.